PROSES BERPIKIR SISWA MADRASAH TIPE QUITTER DALAM PEMECAHAN MASALAH MATEMATIKA BERDASARKAN LANGKAH-LANGKAH POLYA - Nadilla Syahfitri; Isnaniah Isnaniah (Universitas Tanjungpura, 2022)
This research background is found problems in class VII MTs N 2 Bukittinggi such as learning process student difficult finished math problems, fighting power in solving math problems is low, and students math problem solving ability is low too. This research goals is describe the thinking process of quitter students in solving math problems at class VII MTsN 2 Bukittinggi with Ploya’s steps, namely: understand the problem, devise a resolution plan, solve the problem according to the plan, and look back the result obtained. The type of research used is descriptive qualitative with 2 subject quitter students, selected by Adversity Quotient questionnaire and purposive sampling. Data collection using mathematical problem solving test techniques and interviews based on mathematical problem solving on comparison lesson. The validity of the data is checked by Miles & Huberman such as: data reduction, data display, and conclusion. The results show that: (1) Thinking process of quitter student in understanding the problem is an assimilation thinking process. (2) Thinking process of quitter student in devising a problem-solving plan is an imperfect accommodation thinking process. (3) Thinking process of quitter student in carrying out the plan is an assimilation thinking process. (4) In looking back the result have been obtained there is nothing thinking process.